10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Understanding intention to test for HIV reflects readiness for action and provides an opportunity for intervention before behaviour is actualised. In sub-Saharan Africa (SSA), HIV testing remains low. While numerous studies have identified factors influencing HIV testing, less is understood about how these factors shape the intention to test. Guided by the Theory of Planned Behaviour (TPB), this study examined HIV testing intention among heterosexual males in Bolgatanga Municipality. A community-based cross-sectional survey included 480 heterosexual males. Data were collected using structured questionnaires and analysed with STATA 17 and IBM SPSS AMOS 29. Statistical procedures included descriptive statistics, chi-square tests, logistic regression, confirmatory factor analysis (CFA), and structural equation modelling (SEM). Model fit was assessed using the Adjusted Goodness-of-Fit Index (AGFI), Comparative Fit Index (CFI), Goodness-of-Fit Index (GFI), Incremental Fit Index (IFI), Normed Fit Index (NFI), and Root Mean Square Error of Approximation (RMSEA). Based on a predefined mean score of ≥3.0, only 13.3% (95% CI: 10.3 - 16.4) of participants expressed a strong intention to test for HIV; 46.5% had positive attitudes, 57.7% reported high subjective norms, and 2.1% had high perceived behavioural control (PBC). Multivariate analysis revealed that positive attitudes (AOR = 1.55), high subjective norms (AOR = 2.23), and high PBC (AOR = 2.97) increased the odds of strong intention. Younger age groups had lower odds of intention, while frequent media exposure predicted higher intention. Psychometric evaluation confirmed excellent internal reliability (ω ≥ 0.96), and SEM indicated good model fit (AGFI = 0.862; CFI = 0.926; RMSEA = 0.060). PBC emerged as the strongest direct predictor (β = 0.45). HIV testing intention was influenced by psychological, social, and structural factors. Improving HIV testing among heterosexual men requires interventions that strengthen PBC, leverage supportive social norms, and expand sustained media engagement to reduce barriers and normalise HIV testing.